2011
DOI: 10.1016/j.seizure.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Epileptiform response of CA1 neurones to convulsant stimulation by cyclothiazide, kainic acid and pentylenetetrazol in anaesthetized rats

Abstract: We have previously reported that cyclothiazide (CTZ) evokes epileptiform activities in hippocampal neurons and induces seizure behavior. Here we further studied in vivo the sensitivity of the hippocampal CA1 neurons in response to CTZ in epileptogenesis in comparison with two other classic convulsants of kainic acid (KA) and pentylenetetrazol (PTZ). CTZ administered intracerebral ventricle (i.c.v.) induced epileptiform activities from an initial of multiple evoked population spikes, progressed to spontaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Using this model, our results demonstrated that extrasynaptic GABA A Rs were downregulated by ~50% Recently, several studies have shown that CTZ is a potent convulsant capable of inducing epileptiform activity both in vivo and in cultured hippocampal neurons [16,17,25] , as well as evoking seizure behavior in freely-moving animals [26] . In the current study, we further extended this epilepsy model to hippocampal slices.…”
Section: Discussionmentioning
confidence: 64%
“…Using this model, our results demonstrated that extrasynaptic GABA A Rs were downregulated by ~50% Recently, several studies have shown that CTZ is a potent convulsant capable of inducing epileptiform activity both in vivo and in cultured hippocampal neurons [16,17,25] , as well as evoking seizure behavior in freely-moving animals [26] . In the current study, we further extended this epilepsy model to hippocampal slices.…”
Section: Discussionmentioning
confidence: 64%
“…The hippocampal CA1 region is one of the brain areas in which PTZ induces highly synchronized epileptiform burst activity31. We therefore hypothesized that a reduced PTZ seizure threshold would be reflected in an increased excitability of CA1 pyramidal neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The acute models mentioned elsewhere in this review use slices of hippocampus and other forebrain structures maintained in vitro or in vivo (Prince, 1972;Qian et al, 2011;Stafstrom et al, 2009;Tabashidze and Mares, 2011). Many of them rely on blocking GABA A receptor mediated inhibition with drugs such as picrotoxin, bicuculline or penicillin (Dingledine and Gjerstad, 1979;Schwartzkroin and Prince, 1978).…”
Section: Acute Models Of Epilepsy-convulsant Drugsand Changes In Extrmentioning
confidence: 99%